2015
DOI: 10.4314/jmbs.v4i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge level of cervical cancer among women of reproductive age in Bolgatanga municipality

Abstract: This study assessed the awareness and knowledge level of cervical cancer among reproductive women in the Bolgatanga Municipality of the Upper East Region of Ghana. A structured questionnaires was used to gather data from one hundred and fifty (150) women. The participants were recruited using the convenient sampling method. Out of the total number of 150, 50% of the women were between 21 and 29 years old whiles 14% were aged 15-20 years. The findings suggest that 70.7% of the participants have ever heard of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…There is however an indication that current sensitization programmes are yielding results; this might have accounted for the considerable number of women (61.3%) adequately aware about cervical cancer. This compares with an average awareness rate reported by Ziba et al [5] in…”
Section: Respondents' Perceptions About Cervical Cancersupporting
confidence: 80%
See 3 more Smart Citations
“…There is however an indication that current sensitization programmes are yielding results; this might have accounted for the considerable number of women (61.3%) adequately aware about cervical cancer. This compares with an average awareness rate reported by Ziba et al [5] in…”
Section: Respondents' Perceptions About Cervical Cancersupporting
confidence: 80%
“…Among health workers in Winneba-Ghana, it was found that this group of women had adequate knowledge about the risk factors of cervical cancer [7], and it was therefore not surprising that the participants in that study did well on this same question than those in the current study. However, the findings of this study regarding the question about risk factors were similar to those among women of reproductive age in Bolga-Ghana [5] and sexually active women in Elmina-Ghana [13] who were not health workers in both studies and therefore could not have been adequately informed about cervical cancer.…”
Section: Barriers To the Practice Of Cervical Cancer Screeningmentioning
confidence: 53%
See 2 more Smart Citations
“…Similarly a link between formal education and awareness of cervical cancer was observed in a study conducted in Ghana. 15 …”
Section: -14mentioning
confidence: 99%